SIWAK: Between Needs and Lifestyle - Dedisyah Putra (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2021)
Every individual who acts as a Public Figure wants to be able to appear perfectly in front of the public. So that everything needs to be prepared as well as possible so as not to become disabled in the eyes of those who see it. Among the appearances that must always be considered are the appearance of clean, bright teeth and a mouth that smells good and fresh. This research will summarize the virtues of bersiwak using the siwan tree (arac) and other types of siwak made from chemicals from various literatures that are adapted to the scientific and legal perspective of Islam. In addition to using literature review, this analysis is also a descriptive study / research to provide a complete picture of the law and the impact of miswak for social life, seeing that each individual should pay attention to a clean, healthy and worship-worthy lifestyle by Allah Ta'ala.Keywords: Islamic Law, Siwak, Lifestyle